Faktor-Faktor yang Mempengaruhi Penggunaan QR Code pada Era Digitalisasi dengan Metode Usability - Rachmat Suryadithia (Paradigma, 2013)
QR Code is a"bridge" connecting quickly between content offline and online content.QuickResponseCodeisabarcodeexpress the conceptofdevelopment, whichfocuses onreadingspeedincharacters. The purposeofthis study wasto measurethe extent to whichthe general public,especially in Indonesia, knows andto implement the2Dcodetechnologyin the era ofdigitalization,viewed fromfour perspectives:usefulness(utility), ease of use(ease of use), easeoflearning(ease inthestudy) andsatisfaction(satisfaction). Measurement methodsused inthis studyusingaquestionnairetypeUSEusability. The results showthat theQRCodeinIndonesiais veryuseful, butstillconstrainedin howto useQRCode, due tothe small numberpeopleinIndonesiaknowQRCodeitself,from how to maketheQRCodeGeneratortohow to readQRCode. Expectedmorefor the futureofmediasocializationin the use ofQRCodetechnology utilizationinIndonesiansociety.Keywords: QR Code, the era of digitalization, Usability.